Indigenous Knowledge on the Use and Management of Medicinal Trees and Shrubs in Dale District, Sidama Zone, Southern Ethiopia - Kewessa, Gonfa; Abebe, Tesfaye; Demessie, Ambachew (Ethnobotany Research and Applications, 2015)
Plants (both wild and cultivated) are essential to alleviate human health problems and food insecurity especially in the developing world. The present study was conducted in Dale District, Sidama Zone, Southern Nations, Nationalities, and People’s Region, Ethiopia, from February 2012 to June 2012, with an objective to (1) identify tree and shrub species used as medicines for the treatment of human and livestock diseases and sources of these medicinal species and (2) document factors associated with indigenous knowledge on their utilization and conservation. A total of 63 informants were involved. Data were collected using semi-structured interviews, field observations, and farm inventories. Forty-two medicinal tree and shrub species were used to treat 34 human diseases and 15 livestock diseases. The most frequently used part was leaves. The most widely used method of remedy preparation is crushing. The common route of administration is oral which is applied through drinking. Agricultural land expansion, wood for construction, timber production, and firewood collection are the major threats to those species. Except for some cultural and spiritual beliefs supporting conservation, efforts to conserve and cultivate medicinal species are limited in the area. Therefore, participation of the local people, awareness-raising through training on judicious utilization, and conservation of these species is important.